Chapter Cartesian and Malebranchian Meditations - Carbone, Raffaele (Knowledge and its Histories, 2023)
In his Christian and Metaphysical Meditations (1683) Malebranche develops a reflection in which the self discovers in its interiority that the interlocutor able to answer some of its questions is the divine Word. Through references to the Holy Scriptures and to Augustine, Malebranche constructs a meditative itinerary that differs from the one proposed by Descartes, as it moves from the lumière naturelle in the Cartesian sense to the lumière of the Word. In the light of these historical-theoretical data, we propose a reconstruction of the role played by interiority and meditation in certain texts by Malebranche, highlighting the moments in which he appropriated the Cartesian heritage and those in which he distanced himself from Descartes' philosophical paradigm.